Ảnh hưởng của dòng vốn vào đến tỷ giá thực: Trường hợp các nước Đông Á - Nguyễn Thị Hồng, Vinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The aim of this study is to empirically provide evidence regarding the impact of capital inflows on the real effective exchange rate (REER) in East Asian countries based on the Salter–Swan–Corden–Dornbusch paradigm. Using the fixed-effect model and generalized method of moments (GMM) method, the paper examines the effect of the composition of capital inflows on the real exchange rate in East Asia over the 20052018 period. The results show that different forms of capital inflows affect the real exchange rate in different ways. While foreign direct investment (FDI) has a positive impact on REER, foreign portfolio investment (FPI) has a negative effect on REER. These results imply that an increase in FDI inflows is associated with the real exchange rate appreciation while FPI inflows lead to real exchange rate depreciation. Besides, the real exchange rate is also affected by trade openness, terms of trade, debt, and expenditure. These results recommend that the government of East Asian countries should monitor the capital inflows and have appropriate macroprudential policies under exchange rate pressure
Keywords: Real effective exchange rate; Capital inflows; Dutch disease; East Asia; Dynamic panel data